CODE-SWITCHING IN VIEWER COMMENTS ON AN INDONESIAN EDUCATIONAL YOUTUBE CHANNEL - Caku Caku; Gabriela Apriani Koli; Axel Emmanuel Herman Jr. Kolatlena; Ouda Teda Ena (Journal of English Educational Study (JEES), 2026)
This study investigated code-switching patterns in viewer comments on the Indonesian educational YouTube channel "Kok Bisa." Using a descriptive qualitative content analysis approach, the research examined 103 comments from two science education videos uploaded in October 2025, focusing on code-switching types, languages involved, and communicative functions. The data were analyzed using Poplack's (1980) structural typology and Myers-Scotton's (1993) functional framework. The findings revealed that intra-sentential switching was the most frequent type (64%), followed by inter-sentential (17%), tag-switching (14%), and intra-word switching (5%). The primary languages involved were Indonesian and English, with English predominantly used for technical and scientific terminology. Clarification emerged as the dominant communicative function (40%), followed by emphasis (30%), engagement (20%), and identity expression (10%). The study showed that code-switching in educational YouTube comments served both cognitive-pedagogical and social-interactional purposes, facilitating comprehension of complex content while reflecting the bilingual identity of Indonesian digital youth. These findings contributed to understanding multilingual practices in digital educational spaces.